(untitled) (Research, Society and Development, 2023)
Objective: To know what has been published about the care of the father to the premature newborn. Materials and method: This is an integrative review carried out in the databases Latin American and Caribbean Literature in Health Sciences, Latin American Center and Online System of Search and Analysis of Medical Literature and Cochrane Library, without time limit, in the Portuguese, English and Spanish languages, in order to have a wider range of publications. A total of 62 studies were selected to compose this review. Results: Based on the findings, three themes were developed: Hospitalization of the Premature Newborn in the Neonatal Intensive Care Unit; Initial adaptation and participation of fathers and mothers in the care provided to the Premature Newborn; and Changes in family routine resulting from premature birth. Conclusions: it is necessary to rethink the traditional model of care for newborns based predominantly on maternal participation, and health professionals should incorporate the presence of the father in neonatal units, aiming to implement measures to define and guarantee their effective role in the care of the child.